Navigating social norms and community narratives: a thematic analysis of health communication practices in northern Nigeria - Abraham, Faridah Kwandala (My University, 2026)
Nigeria widely known as the giant of Africa, rich in abundant natural and human resources, and despite its abundant resources, continues to experience severe health inequities, reflected through high mortality rates in women and children and persistently low life expectancy (Matthew Ayodele et al., 2024) These disparities are most pronounced in Northern Nigeria, where factors like religious beliefs, gender norms, stigma , and reliance on spiritual beliefs strongly shape health behaviors and decision-making processes. This study is a deep analysis of the disconnect that exist between dominant health communication strategies and the socio-cultural realities that influence health beliefs and practices in Northern Nigerian communities. Anchored on the Social Norms Theory (Bak et al., 2021) and the Culture-Centered Approach (Dutta, 2008), the research explored the various ways social norms influence health related beliefs and behaviors across maternal and infant health, infectious diseases, and noncommunicable conditions, while assessing the effectiveness of existing health communication practices. Data was collected qualitatively through semi structured interviews and participant observation, and patterns on how health messages were interpreted, legitimized, and acted upon within sociocultural contexts were identified using thematic analysis. Findings from the study reveals that health communication in Northern Nigeria continuously gets filtered through religious and cultural filters. Leaders of faith such as Imams and traditional leaders emerged as the central figures of medical authority, determining if medical information is accepted or dismissed, especially in the contexts where institutional trust in formal health institutions remains fragile. In the same vein, traditional and biomedical knowledge systems coexist, gender hierarchies hindered the agency of women's health and yet community-trusted figures and culturally resonant communication strategies transformed social norms into facilitators of sustained health behavior change. The findings show that strategically engaging with the culturally embedded norms can greatly improve health communication outcomes in complex sociocultural settings.
Keywords: Epistemological; Social norms; Culture centered approach; Theological; Culturally embedded